2020
DOI: 10.1016/j.jiac.2020.06.011
|View full text |Cite
|
Sign up to set email alerts
|

A case report of SARS-CoV-2 confirmed in saliva specimens up to 37 days after onset: Proposal of saliva specimens for COVID-19 diagnosis and virus monitoring

Abstract: We present the case of a 71-year-old man who, despite becoming asymptomatic after having some mild symptoms of COVID-19, had SARS-CoV-2 RNA detected for 37 days after onset, from his concentrated and purified saliva specimens using sugar chain-immobilized gold nanoparticles. It was suggested that the early morning saliva specimens were more likely to show positive results than those obtained later in the day.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 11 publications
1
44
0
2
Order By: Relevance
“…In addition to viral load, the efficiency of saliva collection was investigated and compared with oro-/nasopharyngeal swabs for viral detection. Nine studies reported the sensitivity and/or specificity of RT-qPCR-analyzed saliva specimens as compared with the gold standard diagnosis of throat and nasopharyngeal swabs (NPSs; Azzi, Carcano, Gianfagna, et al 2020; Jamal et al 2020; Leung et al 2020; Nagura et al 2020; Pasomsub et al 2020; Tajima et al 2020; To, Tsang, Yip, et al 2020; Williams et al 2020; Zhu et al 2020), which varied considerably from 66% to 91.7% and from 97% to 100%, respectively. Combined with those results, the cost savings for posterior oropharyngeal saliva collection were analyzed in 1 study and compared with conventional NPS, with the costs of equipment estimated as US $8.24 per 100 saliva specimens as compared with US $104.87 per 100 NPSs (Wong et al 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to viral load, the efficiency of saliva collection was investigated and compared with oro-/nasopharyngeal swabs for viral detection. Nine studies reported the sensitivity and/or specificity of RT-qPCR-analyzed saliva specimens as compared with the gold standard diagnosis of throat and nasopharyngeal swabs (NPSs; Azzi, Carcano, Gianfagna, et al 2020; Jamal et al 2020; Leung et al 2020; Nagura et al 2020; Pasomsub et al 2020; Tajima et al 2020; To, Tsang, Yip, et al 2020; Williams et al 2020; Zhu et al 2020), which varied considerably from 66% to 91.7% and from 97% to 100%, respectively. Combined with those results, the cost savings for posterior oropharyngeal saliva collection were analyzed in 1 study and compared with conventional NPS, with the costs of equipment estimated as US $8.24 per 100 saliva specimens as compared with US $104.87 per 100 NPSs (Wong et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Differences during the day were detected, as were higher viral loads early in the morning versus bedtime (Hung et al 2020). In addition, saliva specimens collected during the day had a lower rate of positive concordance with NPS viral load than saliva collected early in the morning (Tajima et al 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Key advantages of the Simplexa™ COVID-19 Direct assay are simple operation procedures, with an all-in-one reagent mix and high-speed of detection in just over an hour, which is significantly faster than the up to seven hours required by traditional extraction followed by amplification technologies, currently used to detect SARS-CoV-2 RNA in OF samples [ 11 , 12 , 13 , 14 , 15 , 16 , 18 ]. Moreover, the test does not require extra-equipment (i.e centrifuges or an extraction system) and technical laboratory infrastructure, being suitable for the field settings and for near-to-patient diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…To et al, demonstrated that SARS-CoV-2 was present in OF specimen of 11 out of 12 patients, with viral load being higher during the first week after symptoms onset and declining thereafter, being detectable until 25 days after symptoms onset (DSO) [ 14 , 15 ]. In another study, SARS-CoV-2 RNA was detected in OF of one patient for prolonged period, up to 37 DSO [ 16 ]. We evaluated the use of commercial Simplexa™ COVID-19 Direct assay on OF samples from hospitalized COVID-19 patients, for identification of SARS-CoV-2 RNA, duration of viral shedding, and determining the assay specificity and sensitivity on OF samples compared to NPS and BAL samples.…”
Section: Introductionmentioning
confidence: 99%
“…with days from symptom onset, age, sex, and comorbidities, viral load in inverse corr. with inlflammatory index No control, only severe disease patients 3 18 Tajima et al (2020) Single 1, COVID-19 hospitalized pateints, 71 yr M, no control Saliva serial sample each day from 9 to 45 days post infection, both EMSS (from day 28 of ds onset) and DSS(till day 26 of ds onset), 600 µL quantity, using SMGNP, self-collection under supervision RT-PCR Detection of virus in saliva up to 37 d after symptom onset, even after symptoms subside. DSS sensitivity—25.0% and specificity—100%, EMSS sensitivity—66.7% and specificity—100% One patient case report 4 19 Yoon et al (2020) Single 2, COVID-19 hospital inpatients, 46 and 65 yr, 2 F/0 M, no controls Serial saliva sampling every 2 days from hospital days 1–9, additional samples after CLX mouthwash at 0 h(before), 1 h, 2 h, 4 h, self-collection rRT- PCR, CFX96 (Bio-rad, Hercules, CA, USA) and PowerChek 2019-nCoV (Kogenebiotech, Seoul, Korea) Viral load highest in NPS (7.49–8.41 log 10 copies/mL), also elevated in saliva (6.63–7.10 log 10 copies/mL), detection till day 6 of hospital admission (day 9 of illness-2nd patient ), a transient decrease in salivary viral load for 2 h using chlorhexidine MW Sample size small, no controls (no gargling with saline) 5 20 Han et al (2020) Single 27-day-old neonate, mother (confirmed COVID-19), no controls Serial sampling, health personnel rRT-PCR kit (Kogene Biotech, Seoul, Korea) Load of virus in NPS > saliva in early stages of the disease, fall below detectable levels in saliva in approximately 10 d One neonate subject 6 21 Azzi et al (2020) Single 2, 71, and 64 yr M, severe disease, no controls Patient 1: drooling technique, after 10 days of admission, health personnel.…”
Section: Introductionmentioning
confidence: 99%